1986
DOI: 10.1121/1.2023630
|View full text |Cite
|
Sign up to set email alerts
|

Pure-tone sensitivity of human infants

Abstract: The ability of 3-, 6-, and 12-month-old infants to detect pure tones in quiet was tested at frequencies ranging from 250–8000 Hz. Stimuli were presented monaurally via headphone. Signal trials consisted of ten repetitions of a 500-ms tone burst, with 10-ms rise-fall time and 500 ms between bursts; no-signal trials were 10-s intervals of quiet. The infant's response to a tone was judged by an observer, who, blind to trial type, decided whether or not a tone had been presented on each trial, based on the infant'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 0 publications
7
63
0
Order By: Relevance
“…Schneider et al 1989 tested this hypothesis by estimating percent correct for the detection of a tone masked by a 1/3 octave band of noise; psychometric functions from group data failed to show compelling evidence that children's psychometric functions are shallower than those of adults. However, other studies (e.g., Allen and Wightman, 1994;Olsho et al, 1988) have estimated psychometric functions based on individual listeners' data and have found an increase in slope with age, as would be expected if internal noise played a role in the elevated masked detection thresholds of the child listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Schneider et al 1989 tested this hypothesis by estimating percent correct for the detection of a tone masked by a 1/3 octave band of noise; psychometric functions from group data failed to show compelling evidence that children's psychometric functions are shallower than those of adults. However, other studies (e.g., Allen and Wightman, 1994;Olsho et al, 1988) have estimated psychometric functions based on individual listeners' data and have found an increase in slope with age, as would be expected if internal noise played a role in the elevated masked detection thresholds of the child listeners.…”
Section: Introductionmentioning
confidence: 99%
“…The present investigation was designed to address this question by examining infants' ability to detect differences in intensity over a wider range of standard levels. Because previous work has demonstrated that the thresholds of6-to 7-month-old infants are significantly less mature at low than at mid and high frequencies (Olsho, Koch, Carter, Halpin, & Spetner, 1988;Trehub, Schneider, & Endman, 1980), we elected to compare discrimination performance for both 10w-and highfrequency noise bands. Under a number of conditions, thresholds are also less mature at short durations during infancy.…”
Section: Examined Dlsmentioning
confidence: 99%
“…Infants can have thresholds up to 25 dB worse than adults; rapid improvement occurs before the age of 6 months (Tharpe and Ashmead, 2001), with a difference narrowing down to a 10-15 dB gap by the time that children reach 5 years of age. Differences in detecting sounds seem to also depend on the frequency, whereby sensitivity is near adult-like by age 6 months for high-frequency sounds of around 4000 Hz, but not for low-frequency sounds around 500 Hz (Olsho et al, 1988;Trehub et al, 1988). The physiologic basis for this difference has not been identified, and does not appear to result from maturation in conductive properties of the peripheral auditory system or in the sensory development that takes place during infancy and childhood.…”
Section: Detection Of Soundmentioning
confidence: 96%
“…For example, it was well documented that thresholds for detecting stimuli in quiet improve between infancy and early school age (Olsho et al, 1988;Trehub et al, 1988). Infants can have thresholds up to 25 dB worse than adults; rapid improvement occurs before the age of 6 months (Tharpe and Ashmead, 2001), with a difference narrowing down to a 10-15 dB gap by the time that children reach 5 years of age.…”
Section: Detection Of Soundmentioning
confidence: 99%
See 1 more Smart Citation